Building reading classrooms: Insights from educational service contracting schools in the Philippines - Violeta F. Apiles (International Journal of Educational Management and Development Studies)
Reading comprehension is a foundation for lifelong learning. When not honed, this skill greatly affects the learners’ ability to perform complex tasks expected of them to achieve the standards set by any curriculum. This study investigated teachers' experiences in implementing reading comprehension strategies among junior high school students in selected education service contracting schools in Baguio and Benguet in the Philippines using a descriptive research method highlighting the cross-sectional survey research design. Findings disclosed that foundational reading comprehension remains a serious issue, with low literacy levels, limited vocabulary, and varying student abilities cited as major barriers. Teachers highlighted that insufficient instructional time, lack of reading materials, and behavioral issues like disengagement and uncooperative attitudes hinder effective comprehension. The study underscores how diverse student needs, resource constraints, and limited instructional support compel teachers to invest additional time and effort, often resorting to simplified translation and repeated practice. Student attitudes toward reading, aggravated by technology and other distractions, reduce engagement and prevent the development of a robust reading culture. To address these challenges, the study recommends a comprehensive reading support program integrating differentiated instruction, expanded access to reading resources, and adaptive techniques for students with diverse abilities. The program emphasizes the need for behavioral and motivational interventions encouraging active participation and developing a more positive attitude toward reading. By prioritizing resource allocation, professional development, and targeted student engagement, this study provides a framework for improving reading comprehension outcomes and fostering a more inclusive and supportive literacy environment.